Serological evidences link toxoplasmosis with schizophrenia and major depression disorder. Issue 3 (September 2015) - Al-Hussainy, Nabeel H.; Al-saedi, Ahmad M.; Al-lehaibi, Jehad H.; Al-lehaibi, Yasser A.; Al-Sehli, Yasser M.; Afifi, Mohammed A.
Abstract: The etiology of psychiatric disorders is largely unknown. A role of environmental insults during early neurodevelopment have been suggested. Infections are possible risk factors for psychiatric disorders especially Toxoplasma gondii, a neurotropic parasite with a life-long residence in brain. This study has investigated a possible role of toxoplasmosis in the development of schizophrenia and major depression disorder (MDD). The influence of other covariates; age, gender and family history was also studied. A cross-sectional study on a total of 177 individuals, where anti- Toxoplasma IgG and IgM in sera of schizophrenia ( n = 63) and MDD ( n = 39) patients, all fulfilling DSM-5 diagnostic criteria, were compared to healthy volunteers ( n = 55). Toxoplasma positivity was highest (31.75%) among schizophrenics followed by MDD (25.64%) and controls (14.55%). IgG levels were significantly higher in toxo-positive schizophrenics (230.1 ± 22.9) and MDD (220.56 ± 24.8) compared to controls (9.98 ± 1.78). Three patients only, all schizophrenic, have positive IgM antibodies. Age and male gender appear to have positive associations to toxoplasmosis and psychiatric disorders while family history has no obvious additive role. This report is one of few linking Toxoplasma infection to MDD and adds to many suggesting a link between latent toxoplasmosis and schizophrenia.